The China forest products trade: overview of Asia-Pacific supplying countries, impacts and implications - Katsigris, E.; Bull, G.Q.; White, A.; Barr, C.; Barney, K.; Bun, Y.; Kahrl, F.; King, T.; Lankin, A.; Lebedev, A.; Shearman, P.; Sheingauz, A.; et al. (2004)
Over 70 % of China's timber product imports are supplied by countries in the Asia Pacific region, and China is the dominant forest product market for many of these countries. Unsustainable harvesting practices, illegal logging, and negative impacts on community livelihoods plague many of these supplying countries. The countries may be divided into those still harvesting and exporting timber from natural forests on a large scale and those which have gone past their highest levels of natural forest timber harvesting and are now more aggressively pursuing plantation development and processing. Apart from Russia, China's top Asia Pacific timber suppliers could at best maintain current supply, with natural forest resources being depleted in less than 20 years. Resource limits also constrain expansion and/or long-term continuation of processed product export to China. Greater attention and action on the part of governments, market leaders, and international organizations is needed to address negative impacts, shifting supply to a sustainable, legal, and equitable basis and to determine from where China's long-term supply will come.